Synthetic arylquinuclidine derivatives exhibit antifungal activity against Candida albicans, Candida tropicalis and Candida parapsilopsis - Gilbert Ian; de Souza Wanderley; Urbina Julio A; Cammerer Simon; Fernandes Rodrigues Juliany; Ishida Kelly; Rozental Sonia (BMC, 2011)
Abstract Background Sterol biosynthesis is an essential pathway for fungal survival, and is the biochemical target of many antifungal agents. The antifungal drugs most widely used to treated fungal infections are compounds that inhibit cytochrome P450-dependent C14α-demethylase (CYP51), but other enzymes of this pathway, such as squalene synthase (SQS) which catalyses the first committed step in sterol biosynthesis, could be viable targets. The aim of this study was to evaluate the antifungal activity of SQS inhibitors on Candida albicans, Candida tropicalis and Candida parapsilopsis strains. Methods Ten arylquinuclidines that act as SQS inhibitors were tested as antiproliferative agents against three ATCC strains and 54 clinical isolates of Candida albicans, Candida tropicalis and Candida parapsilopsis. Also, the morphological alterations induced in the yeasts by the experimental compounds were evaluated by fluorescence and transmission electron microscopy. Results The most potent arylquinuclidine derivative (3-[1'-{4'-(benzyloxy)-phenyl}]-quinuclidine-2-ene) (WSP1267) had a MIC50 of 2 μg/ml for all species tested and MIC90 varying from 4 μg/ml to 8 μg/ml. Ultrathin sections of C. albicans treated with 1 μg/ml of WSP1267 showed several ultrastructural alterations, including (a) loss of cell wall integrity, (b) detachment of the plasma membrane from the fungal cell wall, (c) accumulation of small vesicles in the periplasmic region, (d) presence of large electron-dense vacuoles and (e) significantly increased cell size and cell wall thickness. In addition, fluorescence microscopy of cells labelled with Nile Red showed an accumulation of lipid droplets in the cytoplasm of treated yeasts. Nuclear staining with DAPI revealed the appearance of uncommon yeast buds without a nucleus or with two nuclei. Conclusion Taken together, our data demonstrate that arylquinuclidine derivatives could be useful as lead compounds for the rational synthesis of new antifungal drugs.